Understanding the bacillary load and host interaction to design a point-of-care test to diagnose tuberculosis - Cardona, Pere-Joan (Frontiers in Tuberculosis, 2023)
Designing of a Point-of-care test to diagnose tuberculosis (TB) is not an easy task. This viewpoint stems from the dichotomous diagnostic approach, based on the bacillary load estimated in latent tuberculosis infection (LTBI), thanks to the isoniazid chemoprophylaxis strategy, as well as the importance of imaging to differentiate between LTBI and TB. It integrates the “TB spectrum” elucidated through positron emission tomography-computed tomography scan (PET-CT) to highlight the dynamic nature of TB lesions. Additionally, it emphasizes the relevance of animal models that support this perspective, including the drainage of bacilli through foamy macrophages, which aids in understanding LTBI and its chemoprophylaxis, and the significance of lung anatomy in TB induction. Especially the role of interlobular septa and the encapsulation process and its role in lung lobe predilection impact disease progression. Moreover, it acknowledges the gender bias in TB, as its incidence is significantly higher in men across various socioeconomic circumstances, suggesting an unidentified biological mechanism. For a comprehensive approach, the impact of stress and cortisol levels is suggested as a new parameter to be considered, given their association with poverty, and social inequity, and their tendency to be higher in men. All this information has to be contemplated when designing an accurate point-of-care test. The test should encompass the complexity of TB and necessarily integrate both bacillary and host response parameters. It also should cover the diagnosis of extrapulmonary TB, and pay attention to immunosuppressed and pediatric population.